ChemInform Abstract: Water‐Solvent Method for the Synthesis of N‐Substituted and N‐, 4‐Disubstituted 1, 8‐Naphthalimides under Microwave Irradiation. Issue 1 (3rd January 2013) - Zhang, Ye; Feng, Shao‐Bo; Wang, Kai; Yi, Xiang‐Hui; Wang, Heng‐Shan; Pan, Ying‐Ming
Abstract Title compounds of type (III) or (V) are prepared by microwave assisted recyclization with amines (II).